Temporal Variability of Rainfall Amounts and Trend Analysis in the Melloulou Watershed - Yassine, Bertal; Youssef, Ben Brahim (European Scientific Journal, ESJ, 2024)
The present study consists in analyzing the temporal variability of rainfall and rainfall trend a statistical analysis of rainfall data in the Melloulou watershed for a half-century chronicle (1970-2020). The objective of this study is to extract all the rainfall characteristics of this period, to extract the rainfall variability and to determine the rainfall trends. The working method is based on a statistical approach to detect the climatic characteristics of the Melloulou basin. The study of the standardized precipitation index (SPI) and the rainfall deficit index (IDF) showed the alternation of very long dry periods with wet periods. The Mann-Kendall test under the RStudio also showed a decreasing rainfall trend.